2017
DOI: 10.1016/j.hsag.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual framework to facilitate clinical judgement in nursing: A methodological perspective

Abstract: The South African health care and education systems are challenged to provide independent, critical thinking nurses who can cope with diversity in a creative way and define their role in a complex, uncertain, rapidly changing health care environment. Quality clinical judgement is an imperative characteristic that newly qualified professional nurses should possess. To accommodate these needs, SANC in line with the SAQA Act, advocated the development of teaching and learning strategies to balance theory and prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…The results of the present study support the idea that theoretical knowledge, complemented by clinical knowledge, contributes to substantiated, personalized, and responsible decision-making, guided by a reflective attitude on and about actions, supported by dialogue that facilitates personal and professional growth, aspects that were stressed by Graan and Williams (41) and Mahmoud and Mohamed (34) . Consequently, the results suggested that students can make clinical judgments by applying a complex process and using domains of knowledge and the decision-making process (6) .…”
Section: Discussionsupporting
confidence: 81%
“…The results of the present study support the idea that theoretical knowledge, complemented by clinical knowledge, contributes to substantiated, personalized, and responsible decision-making, guided by a reflective attitude on and about actions, supported by dialogue that facilitates personal and professional growth, aspects that were stressed by Graan and Williams (41) and Mahmoud and Mohamed (34) . Consequently, the results suggested that students can make clinical judgments by applying a complex process and using domains of knowledge and the decision-making process (6) .…”
Section: Discussionsupporting
confidence: 81%
“…In lower-middle-income countries (LMICs), including South Africa, the midwife’s workload demands are increased by the fluid healthcare system (Baloyi & Mtshali 2018 ). Furthermore, the healthcare systems in LMIC are characterised by complicated and complex maternity cases, the high risk profile of pregnant women, and MMR’s high burden (Baloyi & Mtshali 2018 ; Van Graan & Williams 2017 ; WHO 2019 ). The complexity of the maternity cases in LMICs requires higher-order thinking skills, facilitating an ability to think critically and problem-solving by applying clinical reasoning skills, thereby enabling informed clinical decisions (Baloyi & Mtshali 2018 ; Levett-Jones et al 2012; Van Graan & Williams 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the healthcare systems in LMIC are characterised by complicated and complex maternity cases, the high risk profile of pregnant women, and MMR’s high burden (Baloyi & Mtshali 2018 ; Van Graan & Williams 2017 ; WHO 2019 ). The complexity of the maternity cases in LMICs requires higher-order thinking skills, facilitating an ability to think critically and problem-solving by applying clinical reasoning skills, thereby enabling informed clinical decisions (Baloyi & Mtshali 2018 ; Levett-Jones et al 2012; Van Graan & Williams 2017 ). Newly qualified midwives who are job-ready need to demonstrate capability in providing evidence-based care, practice independently and be accountable for their actions (Netshisaulu & Maputle 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…To achieve effectively the nursing role, they have to combine theoretical knowledge, skills, values, beliefs and attitudes which form the foundation upon which nursing art is based on [18]. According to clients in the FGDs, the right nursing care practice is synonymous to the quality of care and quality of care is derived from quality of the theory learned, practical experience and mentorship which enhance professional competence [19]. The combination of theory and practice has an important role in the education of nursing students and influence the quality of care, competence and professional practice.…”
Section: Discussionmentioning
confidence: 99%